Democracy in Crisis : Why, Where, and How to Respond - Rich, Roland (Points of view (Lynne Rienner Publishers), 2017)
Democracy is in crisis. After the hope engendered by the Third Wave, democracies around the world are beleaguered with threats from multiple sources. What are these threats? Where did they come from? And how can the challenges to democratic governance best be overcome? Grappling with these questions, Roland Rich interprets the danger signs that abound in the United States and Europe, in Asia and the Arab World, in Africa and Latin America, and offers innovative strategies for turning the tide.